Descriptive analysis testing for sensory evaluation - Bleibaum, Rebecca N. (ASTM International, 2020)
"The Second Edition of this Manual on Descriptive Analysis Testing for Sensory Evaluation is sponsored by ASTM International Committee E18 on Sensory Evaluation. Descriptive analysis is a sensory method by which the attributes of a food or product are identified and quantified, using human subjects who have been specifically trained for this purpose. The analysis can include all parameters of the product, or it can be limited to certain aspects, for example, aroma, taste, texture, and aftertaste. Many descriptive analysis methods and method variations are currently employed by sensory professionals. This second edition contains updates on the four previously published methodologies that are widely used: Consensus/Flavor profile, Texture Profile, Quantitative Descriptive Analysis (QDA), and Spectrum, along with two new chapters on Free Choice Profiling and a Summary of Temporal Methods. Novel descriptive test methods are developed and published every year, yet the commonly utilized toolbox of the fundamental methods, such as those outlined in this manual, have changed little over the past decades. What has changed dramatically is the in-depth experience and applications of these methods in industry. This allows the practitioners an opportunity to fine-tune and apply the methodologies across a multitude of industries and product categories. Hence, the need for an updated version of this manual"--